The Novel Functions of High-Molecular-Mass Complexes Containing Insulin Receptor Substrates in Mediation and Modulation of Insulin-Like Activities: Emerging Concept of Diverse Functions by IRS-Associated Proteins - Hakuno, Fumihiko; Fukushima, Toshiaki; Yoneyama, Yosuke; Kamei, Hiroyasu; Ozoe, Atsufumi; Yoshihara, Hidehito; Yamanaka, Daisuke; Shibano, Takashi; Sone-Yonezawa, Meri; Yu, Bu-Chin; Chida, Kazuhiro; Takahashi, Shin-Ichiro (Frontiers in Endocrinology, 2015)
Insulin-like peptides, such as insulin and insulin-like growth factors (IGFs), induce a variety of bioactivities, such as growth, differentiation, survival, increased anabolism and decreased catabolism in many cell types and in vivo. In general, insulin or IGFs bind to insulin receptor (IR) or IGF-I receptor (IGF-IR), activating the receptor tyrosine kinase. Insulin receptor substrates (IRSs) are known to be major substrates of receptor kinases, mediating IGF/insulin signals to direct bioactivities. Recently, we discovered that IRSs form high-molecular-mass complexes (referred to here as IRSomes) even without IGF/insulin stimulation. These complexes contain proteins (referred to here as IRSAP; IRS-associated protein), which modulate tyrosine phosphorylation of IRSs by receptor kinases, control IRS stability and determine intracellular localization of IRSs. In addition, in these complexes we found not only proteins that are involved in RNA metabolism but also RNAs themselves. Thus IRSAPs possibly contribute to modulation of IGF/insulin bioactivities. Since it is established that disorder of modulation of insulin-like activities causes various age-related diseases including cancer we could propose that the IRSome is an important target for treatment of these diseases.